Evaluación del crecimiento de la microbiota intestinal con la adición de (saccharomyces cerevisiae) y su efecto sobre la digestión de nutrientes en cerdos - Aldas Aldaz, Héctor German (2025)
This research work focuses on studying the response of the intestinal microbiota of pigs to the addition of Saccharomyces cerevisiae in the diet, with the aim of evaluating its growth, determining the phylogeny of the bacteria that are influenced by the addition of the probiotic and determining the feed conversion ratio. This research was carried out at the Funorsal pig farm located in the community of Chazojuan belonging to the Salinas Parish of the Guaranda canton, Bolívar Province, Ecuador. 30 pigs in the fattening stage with an average of 45 days of age and 15 kg of weight were used. Samples of intestinal content, DNA extraction and metagenomics were taken. The main microorganisms found on day one of the study at the genus level were Staphylococcus, Acinetobacter, Escherichia/Shigella, Clostridium, Lactobacillus, Corynebacterium, Terrisporobacter, Enterococcus and Streptococcus while the main species found were: Acinetobacter Acinetobacter_lwoffii(X81665), Lactobacillus_gasseri(AF519171), Romboutsia_timonensis (NR_144740.1) and Streptococcus_suis(AF009477), on day 30 of the study it was determined that with the addition of Saccharomyces cerevisiae the genera that increased were Prevotella, Lactobacillus, Faecalibacterium, Escherichia/Shigella and Streptococcus, while at the species level they were: Prevotella_copri(AB064923), Faecalibacterium_prausnitzii(AJ413954), Lactobacillus_gasseri(AF519171) and Lactobacillus_mucosae(AF126738), the feed conversion ratio of the group that was exposed to the probiotic was 2.0 compared to a ratio of 2.2 for the group that was not exposed to the probiotic